Diffraction of light by acoustic waves in crystals - KLESZCZEWSKI, Zygmutnt; WOJEWODA, Marian (Archives of Acoustics, 1976)
Diffraction of light by acoustic waves at high frequencies, i.e. Bragg diffraction, is discussed, and the possibility of investigating the acoustic and acousto-optical properties of crystals using this method is presented. The measuring systems used, measurements of the propagation velocities and absorption coefficients of acoustic waves, and the photoelastic constants for crystals of melt quartz, TiO_2, CaF_2, GeO_20, and LiNbO_3 are presented.